Regulatory T cells inhibit acute IFN-γ synthesis without blocking T-helper cell type 1 (Th1) differentiation via a compartmentalized requirement for IL-10 - Sojka, Dorothy K. (National Academy of Sciences, 2011)
CD4(+)CD25(+)Forkhead box P3 (Foxp3)(+) regulatory T cells (Tregs) control immune responses to self and foreign antigens in secondary lymphoid organs and at tissue sites of inflammation. Tregs can modify the function of many immune cells and have been proposed to block early proliferation, differentiation, and effector function. Acute ablation of Tregs has revealed rapid cytokine production immediately after Treg removal, suggesting that Tregs may regulate effector function acutely rather than regulating the programming for immune function. We developed in vitro and in vivo models that enabled the direct test of Treg regulation of T-helper cell type 1 (Th1) differentiation. CD28 signaling is known to abrogate Treg suppression of IL-2 secretion and proliferation, but our studies show that Treg suppression of IFN-γ during Th1 priming proceeds despite enhanced CD28 signaling. Importantly, during Th1 differentiation, Tregs inhibited early IFN-γ transcription without disrupting expression of Th1-specific T-box transcription factor (Tbet) and Th1 programming. Acute shutoff of effector cytokine production by Tregs was selective for IFN-γ but not TNF-α and was independent of TGF-β and Epstein-Barr virus-induced gene 3. In vivo, Tregs potently controlled CD4 IFN-γ and CD4 effector cell expansion in the lymph node (four- to fivefold reduction) but not Th1 programming, independent of IL-10. Tregs additionally reduced CD4 IFN-γ in the inflamed dermis (twofold reduction) dependent on their production of IL-10. We propose a model for Treg inhibition of effector function based on acute cytokine regulation. Interestingly, Tregs used different regulatory mechanisms to regulate IFN-γ (IL-10–dependent or –independent) subject to the target T-cell stage of activation and its tissue location.